Liquid Crystalline Nanoparticles for Nasal Delivery of Rosuvastatin: Implications on Therapeutic Efficacy in Management of Epilepsy - Mohammad Zubair Ahmed; Urooj A. Khan; Abdul Haye; Nidhi B. Agarwal; Nabil A. Alhakamy; Hani A. Alhadrami; Musarrat Husain Warsi; Gaurav K. Jain (MDPI AG, 2020)
In the present study we investigated the protective role of intranasal rosuvastatin liquid crystalline nanoparticles (Ros-LCNPs) against pentylenetetrazole (PTZ) induced seizures, increasing current electroshock (ICES) induced seizures, and PTZ-induced status epilepticus. From the dose titration study, it was evident that intranasal rosuvastatin (ROS), at lower dose, was more effective than oral and intraperitoneal ROS. The Ros-LCNPs equivalent to 5 mg/kg ROS were developed by hydrotrope method using glyceryl monooleate (GMO) as lipid phase. The high resolution TEM revealed that the formed Ros-LCNPs were cubic shaped and multivesicular with mean size of 219.15 ± 8.14 nm. The Ros-LCNPs showed entrapment efficiency of 70.30 ± 1.84% and release was found to be biphasic following Korsmeyer-Peppas kinetics. Intranasal Ros-LCNPs (5 mg/kg) showed significant increase in latency to PTZ-induced seizures and ICES seizure threshold compared to control and intranasal ROS solution. Additionally, intranasal Ros-LCNPs provided effective protection against PTZ-induced status epilepticus. No impairment in cognitive functions was observed following intranasal Ros-LCNPs. The results suggested that Ros-LCNPs could be an effective and promising therapeutics for the epilepsy management.